Business strengthening training manual - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
In today's dynamic business landscape, small business owners and entrepreneurs encounter a myriad of challenges, with a particular emphasis on the need for practical solutions to enhance soft skills in business management. This comprehensive training manual has been meticulously crafted to tackle these challenges, delving into crucial topics such as branding, packaging, business regulatory requirements, business planning, marketing, entrepreneurship, emotional intelligence, and communication. Its primary objective is to furnish participants with the skills and insights essential for fortifying their business foundations and ensuring sustained success. Each session is thoughtfully designed to address key facets of business development, from cultivating a compelling brand identity to navigating regulatory compliance and fostering effective leadership through emotional intelligence and communication. This endeavour has been made possible through the generous support of CGIAR as part of the Transforming Agrifood Systems in West and Central Africa Initiative, in collaboration with the Agricultural Transformation in Nigeria’s Federal States and Togolese Regions Towards Achieving Zero Hunger Project. Olumodupe Banwo and Daniel Oyewale Abioye oversaw the manual development, with valuable contributions from Iremide Olasope. We extend our sincere gratitude to all contributors and stakeholders for their unwavering support. It is our earnest hope that this manual will serve as a valuable resource, empowering participants to surmount challenges and attain sustainable business growth.